2003
DOI: 10.1002/ccd.10550
|View full text |Cite
|
Sign up to set email alerts
|

Conflicting functional assessment of stenoses in patients with previous myocardial infarction

Abstract: The utility of fractional flow reserve, absolute and relative flow reserve, and intravascular ultrasound may have an impact on decision-making for percutaneous coronary intervention in patients with previous myocardial infarction and microvascular dysfunction. The role for fractional flow reserve, absolute and relative flow reserve, and intravascular ultrasound is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…However, Meuwissen et al [13] demonstrated that variations in microvascular resistance had an impact on the hemodynamic parameters used in the evaluation of a coronary stenosis, with significant increases in microvascular resistance leading to higher FFR values despite an anatomically fixed stenosis. Also, it has been demonstrated that an infarcted myocardial bed is associated with a microvascular injury which can lead to a decreased maximal hyperaemic flow response and the subsequent underestimation of the functional severity of a coronary stenosis [14–16]. The results of the present study showed a higher event rate in patients with previous myocardial infarction in the territory evaluated by FFR measurement, suggesting that a potential overestimation of FFR measurements obtained in an infarcted territory might have contributed to the higher incidence of cardiac events in patients who had revascularization deferral on the basis of borderline FFR values.…”
Section: Discussionmentioning
confidence: 52%
“…However, Meuwissen et al [13] demonstrated that variations in microvascular resistance had an impact on the hemodynamic parameters used in the evaluation of a coronary stenosis, with significant increases in microvascular resistance leading to higher FFR values despite an anatomically fixed stenosis. Also, it has been demonstrated that an infarcted myocardial bed is associated with a microvascular injury which can lead to a decreased maximal hyperaemic flow response and the subsequent underestimation of the functional severity of a coronary stenosis [14–16]. The results of the present study showed a higher event rate in patients with previous myocardial infarction in the territory evaluated by FFR measurement, suggesting that a potential overestimation of FFR measurements obtained in an infarcted territory might have contributed to the higher incidence of cardiac events in patients who had revascularization deferral on the basis of borderline FFR values.…”
Section: Discussionmentioning
confidence: 52%
“…The 5-year risk of cardiac death or myocardial infarction (MI) in patients with normal FFR is Ͻ1% per year and is not decreased by stenting. Treating patients guided by FFR is associated with a low event rate, comparable to event rates in patients with normal noninvasive testing (Table 3) (41)(42)(43)(44)(45)(46)(47)(48)(49)(50).…”
Section: Outcome Of Using Ffr For Intermediate Lesionsmentioning
confidence: 62%
“…However, the MACE rate of these patients may range from 8 to 21% [21][22][23][24][25]. We set out this exploratory study to investigate whether plaque composition could be one of the reasons to explain this occurrence of events if these lesions are left untreated, based on FFR findings.…”
Section: Discussionmentioning
confidence: 99%